Crew preparing whaling schooner Era for winter, Repulse Bay, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1901)
Crew members are apparently at work alongside the whaling schooner Era at Repulse Bay, Hudson Bay, October 15, 1901. This scene is identified as ""showing men and part of the vessel [whaling schooner Era] when taking our anchors up and placing the vessel in position for the winter."" Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as Photo #97, #171. Number 171 is etched into emulsion on lower part of plate. The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.